The effect of radiolabeled nanostructured lipid carrier systems containing imatinib mesylate on NIH-3T3 and CRL-1739 cells - Evren Atlihan Gundogdu; Emine Selin Demir; Meliha Ekinci; Emre Ozgenc; Derya Ilem Ozdemir; Zeynep Senyigit; Makbule Asikoglu (Taylor & Francis Group, 2020)
The aim of current study is to develop new nanostructured lipid carrier systems (NLCSs) containing imatinib mesylate (IMT) and evaluate their targeting efficiency on NIH-3T3 as fibroblast cells and CRL-1739 as gastric adenocarcinoma cells with radiolabeled formulations. Three formulations (F1-IMT, F2-IMT and F3-IMT) were prepared and radiolabeled with 1 mCi/0.1 mL of [99mTc]Tc. The effect of reducing and antioxidant agents on radiolabeling process was evaluated and radiochemical purity of formulations was performed by radio thin-layer radiochromatography (RTLC). The results demonstrated that the radiochemical purity was found to be above 90% for [99mTc]Tc-F1-IMT and [99mTc]Tc-F2-IMT, while radiochemical purity of [99mTc]Tc-F3-IMT was found to be 85.61 ± 2.24%. Also, [99mTc]Tc-F1-IMT and [99mTc]Tc-F2-IMT have better stability in cell medium and saline than [99mTc]Tc-F3-IMT. Targeting efficiency of [99mTc]Tc-F1-IMT and [99mTc]Tc-F2-IMT comparatively evaluated by cell binding studies with [99mTc]NaTcO4 on NIH-3T3 and CRL-1739 cells. The cell binding capacity and targeting/non-targeting cell uptake ratio of these two formulations was found to be higher than [99mTc]NaTcO4 in CRL-1739. It is thought that the knowledge achieved in this study would contribute to using [99mTc]Tc-F1-IMT and [99mTc]Tc F2-IMT as an diagnosis and treatment agents.